Alpha-clustered hypernuclei and chiral SU(3) dynamics. (1st January 2014) - Hiyama, Emiko; Funaki, Yasuro; Kaiser, Norbert; Weise, Wolfram
Abstract: Selected light hypernuclei are studied using an $α $ cluster model approach (the Hyper-THSR wave function) in combination with a density-dependent $Λ $ hyperon–nuclear interaction derived from chiral SU(3) effective field theory. This interaction includes important two-pion exchange processes involving $Σ N$ intermediate states and associated three-body mechanisms as well as effective mass and surface terms arising in a derivative expansion of the in-medium $Λ $ self-energy. Applications and calculated results are presented and discussed for $^{13}_{Λ }$ C and $_{Λ }^9$ Be. The lightest $α $ clustered hypernucleus, $^5_{Λ }$ He, is also discussed in this context.